Effects of binder and compression strength on molding parameters of dental ceramic blocks - Uz, Murat Mert; Aydinoglu, Aysu Karakas; Yoruc, Afife Binnaz Hazar (ELSEVIER SCI LTD, 2020)
Yttria-stabilized dental zirconia ceramic powders were synthesized by chemical precipitation method and then sintered at 1350 degrees C. 3 wt% and 5 wt% PVA were added as a binder. Chemical, phasic, thermogravimetric, and differential thermal and grain size, as well as distribution analyses were performed on synthesized and commercial dental ceramic powders. The synthesized and commercial samples containing different binder ratios were molded using different cold isostatic presses (200, 300, and 400 MPa). Final sintering was performed at 1450 degrees C for 2 h. Density, microhardness, and fracture toughness analyses were performed on all the block samples. In addition, the fracture behavior of sintered blocks was evaluated by electron microscopy. The results showed that the molding force of 400 MPa with 3% binder content was sufficient to achieve the desired mechanical value, and this sample had 6.02 g/cm(3) density, 10.44 GPa hardness, and 6.34 MPa m(1/2) fracture toughness. As the molding force increased, the density and mechanical values of the synthesized powder also increased, yet no marginal changes were observed in the commercial sample.
Keywords: ZrO2, dental ceramic; Block; Cold isostatic press; STABILIZED ZIRCONIA CERAMICS; FLEXURAL STRENGTH; HEAT-TREATMENT; PHASE; TRANSFORMATION; SIZE; Materials Science